Educational Models and Profiles of Teachers of Library Science and Information Science in Venezuela - Pirela Morillo, Johann (2018)
The results of an investigation that had as objective to analyze the predominant educational models in the Schools and Programs of Librarianship and Information Science, of Venezuelan institutions of higher education and the profiles of the teachers who work in such Schools and Programs. Conceptual references included a comparison of models to structure profiles of academics based on the competency approach, since it is the one with the highest incorporation in the curriculum to train professionals in Librarianship and Information Science in Venezuela. Some results report that the highest percentage of teachers surveyed age is in the range of 45 to over 51 years, with a gender balance. This aspect has been changing in recent years, because library teaching in the Country was mostly exercised by women. As for academic training, the highest percentage was in the area of Library and Information Science, but it is interesting to observe the trend towards interdisciplinarity, based on considering areas such as: Social Communication, Literature (Linguistics and Literature) And Engineering. The conclusions indicate that there is relevance between the models of the institutions and the profiles of teachers, who showed interest in the training and pedagogical and didactic updating, as a strategy that reverts to advantages for professional training in the area.